Effectiveness of School-Based Suicide Prevention Programs for Adolescents: A Systematic Review. - Kweon, Young-Ran; Kwon, Young-Mi; Ryu, Hyunsoo (Journal of Korean Academy of Psychiatric & Mental Health Nursing (JKPMHN), 2025)
Purpose: This study aimed to systematically evaluate school-based suicide prevention programs for adolescents, focusing on their impact on suicide attempts, knowledge and attitudes about suicide, and help-seeking behaviors. Methods: A systematic review was conducted following PRISMA guidelines. Databases searched included PubMed, Cochrane Library, EMBASE, PsycINFO, CINAHL, KMBASE, KoreaMed, and ScienceON. Randomized controlled trials of school-based interventions for middle and high school students were included. The Risk of Bias 2.0 tool was used to assess study quality. Results: Out of 1,738 screened records, eight studies met the inclusion criteria. SOS (Signs of Suicide) and SEYLE (Saving and Empowering Young Lives in Europe) programs significantly reduced suicide attempts by 40% and 55%, respectively. Sources of Strength improved help-seeking behavior (ES=0.62, p<.001), though results were inconsistent across interventions. All programs enhanced knowledge and attitudes about suicide, but methodological limitations, such as variability in implementation and reporting, affected reliability. Conclusion: School-based suicide prevention programs effectively reduce suicide attempts and improve awareness but show mixed results for help-seeking behaviors. Standardized, scalable interventions and rigorous evaluations are needed to enhance their impact.